Structural analysis - Hibbeler, R. C. (Upper Saddle River, N.J : Prentice-Hall, 1999)
This book is about: Types of structures and loads; Analysis of statically determinate structures; ...
Keywords: Engineering; Structural analysis; Structural analysis (Engineering)